ANALYSIS OF BATTING CRICKET EXERCISES BEGINNERS JAKARTA’S ATHLETES U-17 - Mastri Juniarto; Rizky Nurulfa (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2021)
Abstract Batting is a major component in the game of Cricket. Batting is collecting value by hitting the ball and holding the ball and running to swap places with other runners, and if the ball hits the stump then the batsman is declared out. This study discusses the analysis of batting techniques in the game of Cricket U-17 beginner athletes in DKI Jakarta. The subjects in this study were novice athletes from Jakarta U-17 athletes, who were junior high and high school students who had just joined the cricket team. The method in this research uses descriptive qualitative research. With a sample of 60 athletes who are members of the Jakarta U-17 beginner athletes. The results showed that, it showed that the category of batting training facilities and infrastructure for U-17 athletes in DKI Jakarta was 86.04% on average. These results illustrate that batting facilities and infrastructure are in very good category. Furthermore, in the category of results of the application of batting training for U-17 athletes in DKI Jakarta, it shows that the average is 74.94%. These results illustrate that the application of batting in the category is good and the results of batting for U-17 athletes in DKI Jakarta show that the average is 53.36%. These results illustrate that the batting in the category is sufficient. The results of field observations and analysis in the Batting Cricket exercise are explained as follows: 1) The results of the training that are not optimal are a form of not being properly absorbed by the Batting exercises performed by the coach. 2) The need to adjust the training program adopted from outside as well as the training model and media used in training, to suit the characteristics of the athlete. 3) Batting is the main component for all Cricket athletes. So every beginner athlete in DKI Jakarta U-17 Cricket must master the maximum technique of Batting Cricket.